PENGARUH SERVICE QUALITY, PRICE, DAN RESTAURANT ENVIRONMENT TERHADAP CUSTOMER LOYALTY MELALUI CUSTOMER SATISFACTION DI RESTORAN JAKARTA - CHANDRA, YIUTO; PRASASTYO, KLEMENS WEDANAJI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research aims to determine the influence of service quality, price and restaurant environment variables on customer loyalty through customer satisfaction variables. The object of this research is the Chinese restaurant